Psychopathological profiles and trends of Italian social network users (Facebook, Instagram, Twitter, and TikTok) - Giulio Perrotta (Annals of Psychiatry and Treatment - Peertechz Publications, 2022)
Background and aims: With the advent of the Internet and social networks, mass communication has become more interactive and geo-dislocated. The present research hypothesizes the existence of a link between the choice of the use of a specific social network by the subject user of the telematics service and his or her eventual psychopathological profile, hypothesizing that: the users of Facebook (FB) have a higher level of neurotic (cluster A) and psychotic (cluster C) dysfunctional traits, while users of Instagram (IG), Twitter (TW) and TikTok (TT) have a higher level of borderline dysfunctional traits (cluster B), according to the PICI model.  Materials and methods: Clinical interview, and administration of the battery of psychometric tests. SPSS, Anova test (with Bonferroni).  Results and discussion: The population sample was selected based on past clinical contacts and voluntary participation through social recruitment, totaling 5.581 participants, divided into four age groups (18-25, 26-37, 38-46, 47-60) and by four different social networks (Facebook, Instagram, Twitter, TikTok). The present research showed that, on average, the selected users in the studied population sample, divided into sixteen subgroups, present in 79.9% of cases a psychopathological personality profile with at least 5 dysfunctional traits among the first three social networks analyzed (Facebook and Twitter with a lower frequency than Instagram, while TikTok users present an average value of 95.5% of cases). Equally distributed are also the hypotheses of affective addiction among users of the four social networks, with an average of 41.7% of cases, although always with higher pathological peaks in the case of Instagram, and even more for Tiktok, which varies with a much higher average of 69.2%. The pronounced dysfunctional tendency found is also confirmed by the tests related to the study of ego defense mechanisms, which in 100% of the psychopathological cases detected with the PICI (Perrotta Integrative Clinical Interviews) model turn out to be markedly dysfunctional, especially concerning the mechanisms of isolation, fixation, identification, denial, repression, regression, omnipotence, idealization and devaluation. The survey on dysfunctional sexual behaviors also found the marked presence of the clinical condition of users, with a mean value of 21.3% for Twitter, 55.9% for Facebook, 57.8% for Instagram, and 81.0% for TikTok; in particular, the presence of pedophilic paraphilia/pederasty is found in Instagram users with a mean value of 28.5% and for TikTok with a mean value of 43.0%. Conclusion: There is a correlation between the preferred profile choice on a specific social network and one's psychopathological personality profile: Facebook users are found to be more oriented on the neurotic (anxious-phobic, somatic and obsessive) and border (borderline and depressive) area, Twitter users are oriented on the border (bipolar, borderline and narcissistic) area, Instagram and TikTok users on the border (bipolar, borderline, histrionic, antisocial, psychopathic and narcissistic) and psychotic (delusional, paranoid and dissociative) area.